"Face the cow": reconnecting to nature and increasing capacities for pro-environmental agency. Issue 1 (1st January 2020) - Raatikainen, Kaisa J.; Juhola, Katja; Huhmarniemi, Maria; Peña-Lagos, Hugo
ABSTRACT: Arts-based practices can support sustainability, combined with research that points out needs for intervention. We practiced environmental sensitivity and dialogic art with fifth-grade school pupils as part of an International Socially Engaged Art Symposium (ISEAS2019). Using arts-based action research methodology, our case study focused on the opportunities of arts-based environmental education in advancing the management of meadows and wood-pastures. We explored nature connectedness and pro-environmental mindsets and behaviors among the pupils and artists/researchers. The artistic results encompassed the dialogic interactions of the intervention, exhibited artworks, and audiovisual documentation. Using the leverage points framework, we detected key levers in conservation of meadows and wood-pastures, based on literature and the current study through a content analysis on the collected reflective materials. The participants emphasized engaging with agricultural nature in multiple ways, through doing and feeling. Arts-based practices allowed participants to recognize their corporality and develop an experiental, expressive, and informed connection with nature. Based on discussions on the general ideologies and values underlying the intervention, we conclude that promoting a stewardship philosophy towards agricultural nature would benefit its conservation. Arts-based environmental education has great potential in advancing such transition, if the multidimensionality of the interaction between people and nature is acknowledged.